Studying the Relationship Between Morphological Characteristics and Ecological Niche Overlap of the Namak Chub (Squalius namak) In the Jajroud River - Hamed Shabanloo; Hadi Poorbagher; Soheil Eagderi (محیط زیست و توسعه فرابخشی)
Introduction: The degree of overlap in ecological niches can indicate the extent of resource sharing and potential interspecific competition. The intensity or effects of resource sharing and competition may also be partially related to species abundance, especially in resource-limited conditions. In this context, adaptive morphological changes can create differences in species performance, ultimately leading to variations in resource utilization. Morphological characteristics such as body shape, fin placement, and mouth orientation in fish have evolved to be compatible with their specific habitats. The namak chub (Squalius) is a recently recognized genus within the Cyprinidae family, and consequently, limited studies have been conducted on it. Therefore, the information obtained from this research can contribute to understanding ecological processes and how the namak chub (Squalius namak) responds to environmental challenges by comparing various patterns in morphological and ecological traits.Materials and Methods: A total of 103 namak chub (S. namak) were sampled from the Jajrood river. To determine ecological niches, nine environmental variables were used. For morphometric studies, photographs of the samples were taken. Using the 2TpsDig software, 13 landmarks were defined on the two-dimensional images. In traditional morphometric analysis, 17 morphometric characters were assessed from the images using ImageJ. Initially, using data from traditional morphometry (total length, fork length, etc.) and k-means clustering, the fish were grouped based on size. The method used for ecological niche overlap was habitat suitability curves. A non-parametric method known as kernel smoothing was used to plot the relationship between each environmental variable and the number of fish at each site. Using PCA, data from geometric and traditional morphometry were combined into a single score. Finally, linear regression was used to examine the relationship between station scores and the average differences in ecological niche overlaps.Results: The river stone diameter showed the highest significant positive correlation with dorsal fin length and pectoral fin length, and the highest significant negative correlation with post-dorsal fin length, caudal peduncle length, and postorbital length. EC and TDS exhibited the highest significant positive correlations with fork length, eye diameter, and snout length, respectively. Based on landmark displacement patterns, the greatest differences were related to landmarks located in the posterior half of the body, although the tip of the snout also demonstrated high variability. The ecological niche overlap curves indicated that the highest overlap occurred for water flow velocity. TDS and EC showed the lowest levels of overlap. Based on the results, it can be argued smaller individuals of this species are more generalized and prefer non-specialized habitats; however, as size increases, specialization occurs, leading to increased overlap in preferred ecological niches and potentially competition among these fish.Discussion: The two studied groups of this species in the Jajrood river have reduced intraspecific competition through habitat preference and resource exploitation. Although high overlap was observed in some parameters, in general, the ecological niche overlap between different groups of these fish was moderate, and this ecosystem has greatly reduced competition by providing the species with preferred habitat. For future studies, it is suggested that the level of food availability and the effect of water physicochemical parameters on the presence of suitable food for sized groups of this species and the impact of environmental parameters on fish in different seasons should be discussed.